The Application of Bioreactors for Cartilage Tissue Engineering: Advances, Limitations, and Future Perspectives - Liwei Fu; Pinxue Li; Hao Li; Cangjian Gao; Zhen Yang; Tianyuan Zhao; Wei Chen; Zhiyao Liao; Yu Peng; Fuyang Cao; Xiang Sui; Shuyun Liu; et al. (Stem Cells International)
Tissue engineering (TE) has brought new hope for articular cartilage regeneration, as TE can provide structural and functional substitutes for native tissues. The basic elements of TE involve scaffolds, seeded cells, and biochemical and biomechanical stimuli. However, there are some limitations of TE; what most important is that static cell culture on scaffolds cannot simulate the physiological environment required for the development of natural cartilage. Recently, bioreactors have been used to simulate the physical and mechanical environment during the development of articular cartilage. This review aims to provide an overview of the concepts, categories, and applications of bioreactors for cartilage TE with emphasis on the design of various bioreactor systems.